Exploring, Experiencing, and Envisioning Integration in US Arts Education (The Arts in Higher Education, 2018)
This book explores the dedication of the New American Colleges & Universities to the purposeful integration of liberal education, professional studies, and civic engagement through the performing, literary, and visual arts. Examples of course level and programmatic integration of the arts are discussed from both an applied practice-based approach and a philosophical framework that posits student benefit from exploring, experiencing and envisioning creativity in their future professions. The authors believe that the development of professional skills in combination with the theoretical aspects of liberal arts curriculum, which traditionally includes music, theatre, art and literature, provides a high quality undergraduate educational experience that uniquely prepares students for adaptability in their careers and engaged citizenship grounded in the ability to think creatively, critically, and ethically.